JUSTICE OF THE HERITAGE 2:1 DISTRIBUTION IN ARTICLE 176 OF ISLAMIC LAW COMPILATION PERSPECTIVE IN ARISTOTLE’S DISTRIBUTIVE JUSTICE THEORY - Rijal, Arhamu (YURIS: Journal of Court and Justice, 2022)
This paper explores the justice of inheritance distribution as outlined in Article 176 of the Compilation of Islamic Law, specifically focusing on the 2:1 distribution ratio. The study addresses the perception of inequality that arises from this distribution, which some individuals view as unjust. To evaluate the fairness of this inheritance model, the research employs Aristotle's Theory of Distributive Justice as a theoretical framework. The methodology utilized is normative legal research, incorporating both statutory and conceptual approaches to analyze the relevant regulations and principles surrounding the 2:1 inheritance distribution. The findings indicate that the 2:1 distribution in Article 176 maintains a value of justice, as the rights allocated to male and female heirs are proportionate to their respective obligations. This conclusion challenges the notion that the distribution is inherently unjust, suggesting instead that it reflects a balanced approach to inheritance that aligns with the principles of justice articulated by Aristotle. The research ultimately contributes to the discourse on Islamic inheritance law by reaffirming the legitimacy of the 2:1 distribution ratio within the context of distributive justice.